Dependence of SYMH Change Rate on Dynamic Pressure during the Main Phases of Storms: A Comparative Analysis of the 2024 May and 2003 November Superstorms - Ming-Xian Zhao; Gui-Ming Le (The Astrophysical Journal)
We denote the variation in the SYMH index during the main phase of a geomagnetic storm as ΔSYMH and the duration of the storm's main phase as Δ t . The ratio ΔSYMH/Δ t represents the averaged rate of change of the ring current throughout the main phase of the storm. We analyzed the ΔSYMH/Δ t ratios during the main phases of the 2024 May superstorm (referred to as storm1) and the 2003 November superstorm (referred to as storm2), followed by a comparison of the solar wind parameters that significantly influenced the main phases of these two events. We discovered that the ΔSYMH/Δ t ratio for storm1 exceeded that of storm2. Additionally, the time integral of the solar wind electric field during the main phase of storm1 was less than that of storm2, which suggests that ΔSYMH/Δ t is not solely determined by the solar wind electric field. Our findings also indicated that the average dynamic pressure during the main phase of storm1 was larger than that of storm2, highlighting the significance of dynamic pressure as a key parameter in influencing the variation of the ring current during the main phase of a geomagnetic storm.